AGROPOLITAN: SUATU KERANGKA BERPIKIR BARU DALAM PEMBANGUNAN NASIONAL? - Nugroho, Iwan (Journal of Indonesian Applied Economics, 2008)
The study is aimed to comprehend Agropolitan framework in developing of nationalpolicy, and specifically its opportunity in East Java Province. Agropolitan is regionaldevelopment that is based on broadly agricultural development in term on-farm, off-farm and the supporting sector.  Until 2003, it has developed 29 agropolitan areas ineach province excluding DKI Jakarta.  Fund sharing contribution for the agropolitandevelopment were (i) cetral government, 10 to 20 percent; (ii) province government,21 to 40 percent; and (iii) regency or municipality government 41 to 60 percent.  InEast Java, Pasuruan and Sidoarjo regency were proposed as agropolitan area basedon  some  reasons  as  follows:  (i)  perform  significant  entrepreneurship  of  humanresources; (ii) in line with the development plan of Agribusiness Market Center inJemundo  Village,  Sidoarjo  Regency;  and  (iii)  provide  a  high  access  to  TanjungPerak harbor and Juanda International Airport.  Both regency areas have resultedleading  commodities  such as  estate  plant  (mangoes, apple,  sugarcane),  fisheries(bandeng), horticulture (high altitude vegetables), livestock (cow-milk and poultry),and wood craft and mebellair (from forest product).Keywords: Agropolitan, East Java, Pasuruan-Sidoarjo, leading commodity